Malaysia–Korea Commodity Trade: Are there Asymmetric Responses to Exchange Rate Changes?1. Issue 2 (1st March 2017) - Bahmani‐Oskooee, Mohsen; Aftab, Muhammad
Abstract : We consider the trade balance of each of the fifty‐five industries that trade between Malaysia and Korea and engage in asymmetry analysis. We find that the short‐run effects of exchange rate changes are asymmetric in all industries. However, significant short‐run cumulative or impact asymmetric effects are established only in thirteen industries and significant adjustment asymmetry in twenty‐one industries. Finally, significant long‐run asymmetric effects were evidenced in eighteen industries which included the two largest industries that engage in more than 20 per cent of trade between Malaysia and Korea. Clearly, the results are industry specific and should be extended to other countries.